2010
DOI: 10.1186/1744-859x-9-31
|View full text |Cite
|
Sign up to set email alerts
|

The 'antisocial' person: an insight in to biology, classification and current evidence on treatment

Abstract: BackgroundThis review analyses and summarises the recent advances in understanding the neurobiology of violence and empathy, taxonomical issues on defining personality disorders characterised by disregard for social norms, evidence for efficacy of different treatment modalities and ethical implications in defining 'at-risk' individuals for preventive interventions.MethodsPubMed was searched with the keywords 'antisocial personality disorder', 'dissocial personality disorder' and 'psychopathy'. The search was l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…In particular, people with an antisocial or borderline PD have been found to be more likely to commit crimes [11]. Assessment of the diagnosis of antisocial PD even requires criminal of unlawful behaviour to have taken place [7,8,12]. Some studies have suggested that particular PD features may lead to a certain kind of criminality, for example that subjects with antisocial PD engage more in crimes against property, whereas subjects with borderline PD are seen as emotionally unstable and impulsive, which may lead to physical violence [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, people with an antisocial or borderline PD have been found to be more likely to commit crimes [11]. Assessment of the diagnosis of antisocial PD even requires criminal of unlawful behaviour to have taken place [7,8,12]. Some studies have suggested that particular PD features may lead to a certain kind of criminality, for example that subjects with antisocial PD engage more in crimes against property, whereas subjects with borderline PD are seen as emotionally unstable and impulsive, which may lead to physical violence [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…4The unsystematic reviews are Abracen et al, 2008; Bailey, Sehgal, Coscia, & Shelton, 2015; D’Silva, Duggan, & McCarthy, 2004; de Ruiter et al, 2016; Doren & Yates, 2008; Gacono et al, 2001; Garrido, Esteban, & Molero, 1995; Harris & Rice, 2006; Hecht et al, 2018; Polaschek, 2014; Polaschek & Daly, 2013; Polaschek & Skeem, 2018; Reidy et al, 2013; Rodrigo, Rajapakse, & Jayananda, 2010; Rosenfeld, Howe, Pierson, & Foellmi, 2015; Salekin, 2002; Salekin et al, 2010; Shaw & Porter, 2012.…”
mentioning
confidence: 99%
“…5 , 49 Although ASPD and psychopathy diagnoses are based on different assessment tools, the distinction between those two is not completely clear. 50 , 51 We consider our study sample relatively homogenous as the participants were all criminal offenders and had a convergent diagnosed ASPD. However, to further study the behavioral origin of our genome-wide significant hit, rs4714329, we investigated its association individually with each of the SCID II items used in this study.…”
Section: Discussionmentioning
confidence: 99%